THE CONCEPT OF CIVIL LIABILITY - Baghdasaryan, Hayk (State and Law, 2023)
The notion of civil liability is a crucial one in civil law. A correct explanation of this idea is immensely practical in addition to its theoretical significance, as it allows for the accurate outline of both legal draft and law enforcement actions, as well as the execution and maintenance of the subjective rights of participants in civil turnover. This article discusses the concept of civil liability, as well as its signs and manifestations. Based on the distinguishing characteristics and symptoms of civil liability, the role of civil liability in the system of legal liability is defined, and the concept of civil liability is formulated.